Quantum Circuits as Minimal Models of Many-Body Dynamics - Foligno, Alessandro (2024)
Quantum circuits have recently gained popularity as models of many-body dynamics. In this work, I focus on specific models of quantum circuits, which allow for exact results, studying several different indicators of the many-body dynamics.